2018
DOI: 10.1051/e3sconf/20187314005
|View full text |Cite
|
Sign up to set email alerts
|

Youthizen, Political Literacy, and Social Media

Abstract: The engagement between young generation and social media in Indonesia is crystal clear. On the one hand, politicians are aware that social media is an efficient and effective medium for interacting with society. It can be seen that, there's open chance for politician to embrace social media as their medium to interact with "youthizen" (youth netizen). This research aimed to describe the role of social media in building the political consciousness of the young generation. By using mixed methods (survey for quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 3 publications
0
10
0
1
Order By: Relevance
“…After socialization, the attitudes showed that Generation Z has greater potential to share political expression in social media than ever before. In research before socialization, Generation Z tends to keep their social media timeline clear of political issues, either from themselves or from their networks on social media (Lailiyah, Yuliyanto, and Pradhana 2018). They prefer to discuss politics in everyday life with their families (63%).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After socialization, the attitudes showed that Generation Z has greater potential to share political expression in social media than ever before. In research before socialization, Generation Z tends to keep their social media timeline clear of political issues, either from themselves or from their networks on social media (Lailiyah, Yuliyanto, and Pradhana 2018). They prefer to discuss politics in everyday life with their families (63%).…”
Section: Resultsmentioning
confidence: 99%
“…Behaviour levels indicate the level of one"s involvement in the issue and the surrounding political events. Political issues and events are not merely based on political campaigns or elections, but also the government"s policies (Lailiyah, Yuliyanto, and Pradhana 2018).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations